Development of Learning Cycle 5E-Based Teaching Tools to Facilitate Students' Conceptual Changes in Mathematics Learning - Ega Gradini; Susanti Susanti (Universitas Jambi, 2022)
This article describes the results of developing Learning Cycle 5E teaching tools that are valid, practical, and effective to facilitate students' conceptual changes in Statistics and Data Presentation material. The Four-D model was used to develop this research. The quality of the product is measured through the validity, practicality, and effectiveness of teaching tools. The device's validity is measured by its relevance and consistency using expert judgment. The device's practicality was measured using a practicality assessment questionnaire, distributed to 5 Mathematics teachers and 20 eighth-grader. Effectiveness was measured through a small group trial involving 1 Mathematics teacher and 28 eighth-grader students. The results showed that the teaching tools developed met the validity, practicality, and effectiveness criteria. Learning tools are declared valid, with the validity score for lesson plans being 0.89, student worksheets being 0.86, teacher book being 0.78, and student book being 0.80. Learning tools are declared practical with a practicality score where the teacher's response is 80.31% in the practical category, and the student's response is 79.19% in the practical category. Furthermore, teaching tools were declared effective with the criteria; the classical average of student learning outcomes reached 83.71, the Learning Completeness Criteria reached 82.14%, the level of teacher learning management was at a Good level, and student activity reached 72.5%.